2004
DOI: 10.1007/s00192-004-1238-5
|View full text |Cite
|
Sign up to set email alerts
|

Tension-free vaginal tape: a prospective subjective and objective outcome analysis

Abstract: The purpose of this prospective study was to describe the effects of the tension-free vaginal tape (TVT) procedure on subjective and objective outcomes. Eighty-seven women (aged 31-95 years) underwent a TVT procedure and were followed for up to 24 months using the Incontinence Impact Questionnaire (IIQ-7), Urogenital Distress Inventory (UDI-6), and a Patient Satisfaction Questionnaire. IIQ-7 scores improved from a mean 51.1 before surgery to 12.7 at 1 month (p<0.001) indicating reduced impact of incontinence o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…A previous study reported on the assessment of 87 patients using a Patient Satisfaction Questionnaire (PSQ) at 24 months postoperatively [21]. That study found that 95.5% of patients were somewhat or completely satisfied with their progress, and that the majority of patients were satisfied despite the presence of irritating voiding symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study reported on the assessment of 87 patients using a Patient Satisfaction Questionnaire (PSQ) at 24 months postoperatively [21]. That study found that 95.5% of patients were somewhat or completely satisfied with their progress, and that the majority of patients were satisfied despite the presence of irritating voiding symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…In 1 study of 809 women who underwent tension-free vaginal tape procedures for SUI, UDI-6 scores decreased by 60.3% (from 58% to 23%) and IIQ-7 scores decreased by 79.3% (from 58% to 12%) at 6 months postoperatively 42 . In another study of 87 women who underwent tension-free vaginal tape procedures, UDI-6 scores decreased by 64.6% (from 61.8% to 21.9%) and IIQ-7 scores decreased by 75.1% (from 51.1% to 12.7%) at 1-month follow-up 43 . This does not suggest that both therapies are equally efficacious, but reductions in standardized questionnaire scores noted for both treatments show that each offers some therapeutic benefit and symptom relief for patients.…”
Section: Discussionmentioning
confidence: 95%
“…Most reports support roughly a 70% to 80% improvement that is sustained over time. 2,12,13 Analysis of the SISTEr trial comparing Burch vs. Sling showed a 78% improvement after both procedures, maintained up to 2 years. 13 …”
Section: Discussionmentioning
confidence: 96%